Nonlinear Wavefront Control by Geometric‐Phase Dielectric Metasurfaces: Influence of Mode Field and Rotational Symmetry. Issue 9 (28th February 2020) - Liu, Bingyi; Sain, Basudeb; Reineke, Bernhard; Zhao, Ruizhe; Meier, Cedrik; Huang, Lingling; Jiang, Yongyuan; Zentgraf, Thomas
Abstract: Nonlinear Pancharatnam–Berry phase metasurfaces facilitate the nontrivial phase modulation for frequency conversion processes by leveraging photon‐spin dependent nonlinear geometric‐phases. However, plasmonic metasurfaces show some severe limitation for nonlinear frequency conversion due to the intrinsic high ohmic loss and low damage threshold of plasmonic nanostructures. Here, the nonlinear geometric‐phases associated with the third‐harmonic generation process occurring in all‐dielectric metasurfaces is studied systematically, which are composed of silicon nanofins with different in‐plane rotational symmetries. It is found that the wave coupling among different field components of the resonant fundamental field gives rise to the appearance of different nonlinear geometric‐phases of the generated third‐harmonic signals. The experimental observations of the nonlinear beam steering and nonlinear holography realized in this work by all‐dielectric geometric‐phase metasurfaces are well explained with the developed theory. This work offers a new physical picture to understand the nonlinear optical process occurring at nanoscale dielectric resonators and will help in the design of nonlinear metasurfaces with tailored phase properties. Abstract : Spin‐dependent geometric‐phases generated through the third‐harmonic generation process occurring in all‐dielectric metasurfaces with different in‐plane rotational symmetries have been theoretically and experimentally studied. Experimental results can be well understood with the developed theory of the nonlinear polarizations, which counts the wave coupling among different components of confined fundamental waves, and be numerically verified by full‐wave simulations.